Jian gou Android ying yong cheng shi : shi yong HTML, CSS he JavaScript : di er ban = Building Android apps with HTML, CSS, and JavaScript : second edition - Stark, Jonathan, 1968- (GoTop Information, Inc., 2012)
Detailed summary in vernacular field.